Deskripsi Kesalahan Pengoperasian Bentuk Aljabar Berdasarkan Gaya Belajar Visual - Abdurahman Hamid (EQUALS: Jurnal Ilmiah Pendidikan Matematika, 2025)
This research is a descriptive study with a qualitative approach which aims to describe misconceptions in the operation of algebraic forms based on students' learning styles. The focus of this research is to identify and analyze the types of misconceptions experienced by students with a visual learning style in understanding algebra concepts. The subject of this research was a student in class VIII-A at SMP LPP UMI in the 2023/2024 academic year who had a visual learning style. The validity of the data in this research was obtained through time triangulation techniques to ensure the consistency and validity of the findings. The instruments used in the research include learning style tests to measure students' learning preferences as well as concept understanding tests equipped with the Confidence Rating Index (CRI) to identify misconceptions experienced by students in more depth. The results showed that the research subjects, coded as AZ, experienced various misconceptions in the operation of algebraic forms. These misconceptions include errors in providing examples and non-examples of a concept, difficulties in simplifying algebraic forms in various forms of mathematical representation, as well as obstacles in selecting and applying appropriate procedures or operations. Apart from that, subjects also experience problems in applying concepts or algorithms to solve mathematical problems systematically. These findings indicate that visual learning styles can influence the way students understand algebraic concepts, especially in connecting visual representations with symbolic concepts. Therefore, more adaptive learning strategies are needed, such as using more interactive visual media, diagrams, or color-based approaches, to help students with a visual learning style understand algebra concepts more effectively and minimize the risk of misconceptions.